Curing kinetics and morphology of a nanovesicular epoxy/stearyl-block-poly(ethylene oxide) surfactant system. Issue 31 (21st August 2015) - Bogaerts, K.; Lavrenova, A.; Spoelstra, A. B.; Boyard, N.; Goderis, B.
<x xml:space="preserve">Abstract</x> Adding blockcopolymer slows down the epoxy curing kinetics and plasticizes the final product. The blockcopolymer vesicular wall structure alters during epoxy curing.